2017
DOI: 10.3144/expresspolymlett.2017.83
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on long term stability of self-healing epoxy coating with different inorganic nanotubes as healing agent reservoirs

Abstract: Abstract. Self-healing epoxy coatings were prepared with different nanotubes as reservoirs for epoxy monomer (healing agent). The nanotubes selected for the current study were TiO 2 nanotubes with two different tube diameter (TNT1 and TNT2) and naturally occurring hallyosite nanotubes (HNT). These self-healing coatings were subjected to accelerated weathering exposure. The weathering stability of the coatings were observed. The surface morphology, chemical changes and surface roughness were studied as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…In case of nanocomposite coatings (Figure 5d), the peaks at 827, 919, 1037, 1452, 1508, and 2922 cm −1 are assigned to oxirane, stretching of oxirane, stretching of C–O–C of ether, –CH 3 deformation, and C–C aromatic, respectively, which are in accordance with the previous results [45,46,47]. The FTIR analysis confirms the successful loading of NaNO 3 into HNTs and encapsulation of linseed oil in UFMCs leading to the development of nanocomposite coatings upon their reinforcement into the epoxy matrix.…”
Section: Resultssupporting
confidence: 91%
“…In case of nanocomposite coatings (Figure 5d), the peaks at 827, 919, 1037, 1452, 1508, and 2922 cm −1 are assigned to oxirane, stretching of oxirane, stretching of C–O–C of ether, –CH 3 deformation, and C–C aromatic, respectively, which are in accordance with the previous results [45,46,47]. The FTIR analysis confirms the successful loading of NaNO 3 into HNTs and encapsulation of linseed oil in UFMCs leading to the development of nanocomposite coatings upon their reinforcement into the epoxy matrix.…”
Section: Resultssupporting
confidence: 91%
“…These findings are consistent with the previous literature [42,43,50,52,53]. It has been reported that the decrease in the band intensities, chain scissoring, and loss of cross-linkage occur due to weathering of the epoxy coating in the natural environment [54][55][56][57]. Bellenger and Verdu has reported the formation of ketone products by the carbonyl band at 1728 cm −1 , while Paterson has reported the aldehyde-based products [58,59].…”
Section: Controlsupporting
confidence: 91%